Colloidal synthesis of SnS nanocrystals with dimension-dependent photoelectrochemical properties. (30th April 2019) - Wu, Yuxuan; Wei, Tingcha; An, Xiaoqiang; Liu, Li-Min
Abstract : SnS nanocrystals synthesized by the colloidal injection method exhibited dimension-dependent photocathodic behaviour for photoelectrochemical applications. Abstract : A crucial obstacle to photoelectrochemical (PEC) water splitting is the scarcity of p-type photocathodes with superior charge separation ability. Nanocrystals with well-defined anisotropic shapes offer an exciting opportunity for tailoring the PEC performance of semiconductors. In this paper, various SnS nanostructures with different dimensions were controllably synthesized using a colloidal injection method. Through controlling the roles of 1-dodecanethiol (DDT) and thioacetamide for nanocrystal nucleation and growth, different morphologies of SnS nanostructures were fabricated. 0-D SnS nanoparticles (NPs) were fabricated by the hot-injection method, while temperature-controlled cool-injection facilitated the formation of 1-D SnS nanorods (NRs) and 2-D SnS nanosheets (NSs). Due to the efficient charge transfer and separation, photocathodes fabricated from 1-D nanorods exhibited much superior activity than 0-D nanoparticles and 2-D nanosheets. Our research demonstrates the enormous potential of dimensional tailoring of anisotropic SnS nanostructures for PEC activity.